2020
DOI: 10.1186/s43088-020-00071-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of using bioactive plant products in the management of Fusarium oxysporum f.sp. albedinis: the causal agent of Bayoud disease on date palm (Phoenix dactylifera L.)

Abstract: Background “Bayoud” disease caused by Fusarium oxysporum f. sp. albedinis (Foa) poses a serious threat to date palm (Phoenix dactylifera L.) in Morocco. However, research studies performed to discover biological methods to control this disease remain limited. The present study has set objectives to determine antifungal activity of five plants extracts (Acacia cyanophylla, Cupressus atlantica, Eucalyptus torquata, Nerium oleander, and Schinus molle) against Foa and link this effect to their content in polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The ability of plant extracts to inhibit mycelial growth was evaluated according to the protocol established by Bouhlali et al [ 1 ]. 5 mm mycelial discs from a 7-day-old culture of M. scaettae were transferred onto Petri dishes containing a PDA medium supplemented with different volumes of plant extracts sterilized through 0.2 μ m millipore filters to obtain 1%, 2%, 3%, and 4% serial dilutions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ability of plant extracts to inhibit mycelial growth was evaluated according to the protocol established by Bouhlali et al [ 1 ]. 5 mm mycelial discs from a 7-day-old culture of M. scaettae were transferred onto Petri dishes containing a PDA medium supplemented with different volumes of plant extracts sterilized through 0.2 μ m millipore filters to obtain 1%, 2%, 3%, and 4% serial dilutions.…”
Section: Methodsmentioning
confidence: 99%
“…The total flavonoid content (TFC) of plant material was measured according to the method previously described by Bouhlali et al [ 1 ]. A sample of five hundred microliters of diluted plant filtrate was filled up to 2500 µ L with distilled water, mixed with 150 µ L of 5% sodium nitrite and 10% aluminum chloride, and then, incubated for 5 min at ambient temperature before adding 1 mL of 1 M sodium hydroxide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…albedinis, F. oxysporum f. sp. cubense not known Isaac and Tahon (2014) , Bouhlali et al (2020) , Akila et al (2011) Animal derived compound showing antifungal activity Cecropin A and CecropinB, Hyalopora cecropia A. flavus, A. niger, A. fumigatus, F. moniliforme, and F. oxysporum Binds to cell wall ergosterol and cholesterol De Lucca et al (1997) Drosomycin D. melanogaster F. oxysporum not known Tian et al (2008) Metchnikowin D. melanogaster Pathogenic ascomycota, including F. graminearum not known Moghaddam et al (2017) Thanatin Podisus maculiveris Neurospora crassa, Botrytis cinerea, Nectria haematococca, Trichoderma viride, Alternaria brassicola, Fusarium culmorum, Ascochyta pisi, Fusarium oxysporum, A. fumigatus and T. mentagrophytes . Inhibition of spore germination and formation of hyphae Fehlbaum et al (1996) Dermaseptins Phyllomedusa sauvagii F. oxysporum and F. moiliformae, Aspergillus flavus, A. fumigetus, A. niger Binds to cell wall ergosterol and cholesterol De Lucca et al (1998) Myticin A and Myticin B Mytilus galloprovincialis F. oxysporum and Escherichia coli D31 not known Mitta et al (1999) Anti-fungal compound identified from other sources Iturin Bacillus velezensis Ralstonia solanacearum and Fusarium oxysporum not known Cao et al (2018) Syringomycin-E Pseudomonas spp.…”
Section: F Oxysporum Infection In Plantsmentioning
confidence: 99%